An??lise das propriedades mec??nicas viscoel??sticas de pulm??es de camundongos descelularizados ap??s terapia fotodin??mica: uma alternativa para o processo de esteriliza????o - Apost??lico, Nadua (2015)
The sterilization step for acellular lungs prior to recellularization is important to ensure that they are free of any risk of transmitting infections from the donor to the recipient tissue/organ to be transplanted. However, there are no data on the mechanical effects induced in the lungs when subjected to a given dose of sterilization radiation through a 660-nm LED. The aim of this study was to evaluate the extracellular matrix (ECM) and lung mechanic parameters of decellularized lungs undergoing photodynamic therapy (PDT) with the purpose of sterilization, and also to perform microbiological analyses of lungs infected with C. albicans to determine the effectiveness of PDT. The lung mechanical evaluation parameters, Resistance (RL) and elastance (EL), exhibited no significant differences between groups. Also, there were no changes observed over time of irradiation, representing a maintenance of the viscoelastic behavior of the lung scaffold after 1h exposure to LED light. The ECM components remained virtually unchanged in the acellular lungs of both groups. We also showed that there was a reduction in fungi infection population after 45 minutes of PDT. However, more studies should be performed to establish and verify the effectiveness of PDT as a possible means for sterilizing lung scaffolds.